2011
DOI: 10.1007/s12011-011-9027-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase-Mediated Apoptosis of Chicken Lymphoblastoid Tumor Cell Line by Lanthanum Chloride

Abstract: To investigate the biological effects of lanthanum on chicken lymphoid tumors, cultures of the MDCC-MSB1 chicken lymphoblastoid cell line were treated with 2.5 mM lanthanum chloride for 2 days at 12-h intervals. The apoptotic cells were detected using the TdT-mediated dUTP nick end labeling assay and flow cytometer analysis. The telomerase activity and the chTERT mRNA expression levels of the MDCC-MSB1 cells were examined. The results showed that MDCC-MSB1 cell apoptosis occurred after incubation for 12 to 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Although it has been previously reported that LaCl 3 affects multiple tumor growth based on cell-based assays and animal experiments ( 10 , 12 14 ), its precise biological role remains largely unclear. Therefore, further investigations on the underlying mechanisms are required.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been previously reported that LaCl 3 affects multiple tumor growth based on cell-based assays and animal experiments ( 10 , 12 14 ), its precise biological role remains largely unclear. Therefore, further investigations on the underlying mechanisms are required.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular production of hydrogen peroxide, according to the concentration, can stimulate either growth or death [56]. Interestingly, low concentrations or short incubation times with lanthanum ion induce ROS formation [19] and stimulate cell proliferation [57], while, on the contrary, longer incubation times and larger concentrations of lanthanum ions inhibit growth and induce apoptosis [57][58][59]. Probably, in the first case, proliferative signalling by ROS is prevailing over proapoptotic conditions generated by massive production of ROS, possibly of mitochondrial origin [19].…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase is a ribonucleoprotein enzyme that adds tandem (TTAGGG)n repeats to the ends of chromosomes in most eukaryotes [ 1 ]. The structure of chicken telomerase, which consists of chicken telomerase reverse transcriptase (chTERT), telomerase RNA component and telomerase-associated protein, is similar to that of human telomerase [ 2 , 3 ]. Telomerase activation is considered a key step in cell carcinogenesis, and telomerase is one of the most commonly used molecular markers for a wide range of malignant tumours [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%